Assistive technologies to maximise independence in people with dementia. Issue 12 (December 2013) - Newton, Lisa; Robinson, Louise
There are about 750 000 people living with dementia in the UK, and this is expected to double in the next 30 years. Dementia care currently costs the UK economy £21 billion per year. The National Dementia Strategy 2009 highlighted dementia as a national priority. It also emphasised the potential for assistive technologies to support people with dementia to live independently, while possibly reducing cost of care through delaying residential care admissions. Assistive technologies cover a wide range of technological solutions to problems encountered by patients with dementia, from tracking devices to simple sink plugs designed to prevent flooding. This article aims to discuss the range of assistive technologies available in dementia care, and their benefits, enabling readers to better signpost patients and their carers to appropriate resources.